Ms1, a novel sRNA interacting with the RNA polymerase core in mycobacteria - Hnilicová, Jarmila; Jirát Matějčková, Jitka; Šiková, Michaela; Pospíšil, Jiří; Halada, Petr; Pánek, Josef; Krásný, Libor (Nucleic acids research, 2014)
Small RNAs (sRNAs) are molecules essential for a number of regulatory processes in the bacterial cell. Here we characterize Ms1, a sRNA that is highly expressed in Mycobacterium smegmatis during stationary phase of growth. By glycerol gradient ultracentrifugation, RNA binding assay, and RNA co-immunoprecipitation, we show that Ms1 interacts with the RNA polymerase (RNAP) core that is free of the primary sigma factor (σA) or any other σ factor. This contrasts with the situation in most other species where it is 6S RNA that interacts with RNAP and this interaction requires the presence of σA. The difference in the interaction of the two types of sRNAs (Ms1 or 6S RNA) with RNAP possibly reflects the difference in the composition of the transcriptional machinery between mycobacteria and other species. Unlike Escherichia coli, stationary phase M. smegmatis cells contain relatively few RNAP molecules in complex with σA. Thus, Ms1 represents a novel type of small RNAs interacting with RNAP.
Keywords: malá nekódující RNA; RNA, Small Untranslated; Mycobacterium; Sigma Factor; Nucleic Acid Conformation; Chromosomes, Bacterial; Mycobacterium smegmatis; syntenie; DNA-Directed RNA Polymerases; sigma faktor; bakteriální chromozomy; DNA řízené RNA-polymerasy; Synteny; konformace nukleové kyseliny